2010
DOI: 10.1089/apc.2009.0312
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel Social Influences on Female Condom Use and Adoption Among Women in the Urban United States

Abstract: Heterosexually transmitted HIV remains of critical concern in the United States and around the world, especially among vulnerable and disadvantaged women, complicated by socioeconomic circumstances, gender power, addiction, and experiences of abuse, among other conditions. Effective woman-initiated HIV prevention options, such as the female condom (FC), are needed that women can use in different sexual relationship contexts. We conducted a behavioral and attitudinal survey with 461 primarily African American a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(54 citation statements)
references
References 33 publications
(38 reference statements)
3
49
1
Order By: Relevance
“…Perhaps the most important findings for women are the role of environmental mastery and autonomy in prevention behavior. Because condom use for women necessitates partner negotiation, these findings are consistent with research into the dynamics of condom use among HIVnegative women which demonstrate the significance of gender-roles and powerdynamics in women's sexual behavior (Weeks et al, 2010). Both environmental mastery and autonomy have been observed to show incremental increase with age (Ryff, 1989).…”
Section: Discussionsupporting
confidence: 80%
“…Perhaps the most important findings for women are the role of environmental mastery and autonomy in prevention behavior. Because condom use for women necessitates partner negotiation, these findings are consistent with research into the dynamics of condom use among HIVnegative women which demonstrate the significance of gender-roles and powerdynamics in women's sexual behavior (Weeks et al, 2010). Both environmental mastery and autonomy have been observed to show incremental increase with age (Ryff, 1989).…”
Section: Discussionsupporting
confidence: 80%
“…Further, Pulerwitz et al (2000) found no evidence of an association between DMD and physical abuse or forced sex. Weeks et al (2010) and Campbell et al (2012) found that African American women tended to have higher DMD scores compared with White women.…”
Section: Resultsmentioning
confidence: 99%
“…Higher relationship control (RC subscale) in women was significantly associated with less intimate partner or dating violence (Campbell, Tross, Hu, Pavlicova, & Nunes, 2012; Pulerwitz et al, 2000; Roye, Tolman, & Snowden, 2012; Tietelman et al, 2008; Volpe, Hardie, & Cerulli, 2012), less sex work (Mosack et al, 2010), higher female condom use (Weeks et al, 2010), and less frequent unprotected vaginal sex (Knudsen et al, 2008; Mosack et al, 2010; Pulerwitz et al, 2000; Roye, Krauss, & Silverman, 2010). RC was not associated with preferred contraceptive method (Beckman et al, 2006), diaphragm use satisfaction (Beckman et al, 2006), or childhood sexual abuse (Mosack et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This model was informed by our prior research on associations in high-risk urban U.S. women among personal (demographic, health status/history, risk behavior and perception, prevention knowledge and attitudes), sex partner-related (relationship number, types and characteristics, abuse history), and peer (perceived influence and norms, network exposure) inputs on FC cognitive factors (knowledge, attitudes) and initial and continued FC use [14]. Though the model was developed and tested with women, we hypothesized the same theoretical relationships among co-factors and first- and second-level outcomes for both men and women in this study.…”
Section: Methodsmentioning
confidence: 99%